2005
DOI: 10.1177/147323000503300210
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Carcinoma and Thyroid Status

Abstract: Gastric carcinoma is reported to be more frequent in geographical areas where diets are either iodine-deficient or iodineexcessive. Reports have also shown an association between thyroid diseases and some of the risk factors for gastric carcinoma. We investigated the frequency of thyroid disorders in 61 patients with gastric carcinoma compared with 55 healthy control subjects. Thyroid health was evaluated by physical examination and by measuring the serum levels of thyroid hormones and thyroid autoantibodies.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 16 publications
5
15
0
1
Order By: Relevance
“…The data of epidemiological studies of coastal population of China and Japan with the highest in the world consumption of iodine (200 mg/daily/ per person due to excessive and harmful consumption of marine algae -sea-weeds) showed the highest rates of gastric cancer incidence (1). The data of Venturi et al (1,6) concerning the relation of iodine and gastric cancer were confirmed in study of Turkish investigators (56).…”
Section: Carcinogenicity Of Iodine and The Compounds Containing Iodinesupporting
confidence: 58%
“…The data of epidemiological studies of coastal population of China and Japan with the highest in the world consumption of iodine (200 mg/daily/ per person due to excessive and harmful consumption of marine algae -sea-weeds) showed the highest rates of gastric cancer incidence (1). The data of Venturi et al (1,6) concerning the relation of iodine and gastric cancer were confirmed in study of Turkish investigators (56).…”
Section: Carcinogenicity Of Iodine and The Compounds Containing Iodinesupporting
confidence: 58%
“…This process is mediated by the Na + /I − symporter (15) and involves similar enzymes with an efficient peroxidase activity (12) (Table 1). Furthermore, besides its essential role for the synthesis of thyroid hormones, iodine regulates the proliferation of gastric mucosal cells (16).…”
Section: Thyroid and Stomach: Embryologic Derivation And Role Of Na+/mentioning
confidence: 99%
“…This notion is supported by the high percentage (12–40%) of positivity of PCA in adult patients with HT (9) which, in turn, is present in approximately 40% of patients with atrophic gastritis (10). Besides the fact that the thyroid and the stomach share some embryological and biochemical features (11), some intriguing similarities have been observed even in the putative pathogenic mechanisms, which characterize the thyrogastric syndrome (12). Furthermore, some specific clinical features characterize or lead to the suspicion of the coexistence of both thyroid and gastric autoimmune (13, 14) disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Immunoblotting studies showed that alterations in TRα protein levels often occur in human gastric cancer (GC) and are associated with distant metastasis [46]. Significant differences were found in the incidence of autoimmune thyroid disease between subjects with GC and control subjects, although neither hyperthyroidism nor hypothyroidism was significantly associated with GC [47]. Correspondingly, another study demonstrated that a substantial number of patients with GC developed antithyroid antibodies, although this was not always associated with diminished thyroid function [48].…”
Section: Gastric Cancermentioning
confidence: 99%